Россия: Вокзал: [Роман] / О. Андреев - Андреев Олег (О России и для России, 2001)
Экземпляры: Камская библиотека (20181203) / Инвентарный номер: 5528 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 65 / ББК: 84(2Рос=Рус)6